A new species of Careproctus (Cottoidei: Liparidae) from the Falkland Plateau, southwestern Atlantic, with COI-based phylogenetic analysis - Villarroel-Perez, Martin L.; Chernova, Natalia V.; Weston, Johanna J. N.; Vukasin, Vedrana; Shcherbich, Zhanna (Zootaxa, 2026)
A new species of snailfish, Careproctus argosgeorgiae sp. nov., is described from the northeastern Falkland Islands, within the Falkland Plateau, in the southwestern Atlantic Ocean. The specimen was collected at a depth of 1680 m during a longline fishing operation and scientific observation deployment conducted by the Falkland Islands Fisheries Department in 2024, in an area of relatively unsurveyed depths known to host Vulnerable Marine Ecosystem (VME) taxa. The new species is distinguished from all 18 known species of Careproctus from southern South America and adjacent subantarctic waters by the following combination of characters: strong pleural ribs; vertebrae 47; dorsal-fin rays 42, anal-fin rays 34, pectoral-fin rays 37; simple teeth; a long gill slit reaching pectoral-fin ray 18; a pelvic disk about 33% of head length; distance from disk to anus not less than the disk length; pectoral-fin upper lobe 67% HL; thick subcutaneous gelatinous tissue; and a uniform light-orange coloration with deeper orange fin and disk margins. Comparative analyses with regional congeners are presented and genetic results are discussed. These findings underscore the importance of continued deep-sea exploration to improve knowledge of the subantarctic ichthyofauna and VMEs.